Treatment of People Condemned to Prison: Theoretical and Empirical Considerations - Simović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
By examining the existing criminological literature, one can observe significant efforts toward studying various forms of inmate treatment, which, if implemented appropriately, can contribute to their rehabilitation and reintegration into everyday life. Considering the prevalence of diverse viewpoints on this subject, the author in this paper addresses key questions characterizing treatment, presenting suggestions and techniques aimed at its improvement, developed by researchers. Questions regarding the actual need for adequate treatment, its impact, and the challenges it entails are at the core of this work, as well as the study conducted in the penitentiary institution in Sremska Mitrovica in October 2022, involving 218 inmates categorized into closed and semi-open departments of the institution. The study is characterized by an anamnestic approach, with the primary data collection instrument being an anonymous questionnaire based on surveys through which the role of different treatment modalities in the reintegration of inmates is examined by considering the inmates perspectives on their contributions and the involvement of treatment officials in their implementation. Emphasis is also placed on assessing the current treatment situation from the perspective of treatment officials. The prevalence of several main treatment modalities and their correlation with changes in inmate groups within the institution’s departments is presented, as well as the connection between motivation for reintegration and the implementation of prescribed treatments. The analysis of the treatment officials’ questionnaires demonstrated their training and dedication and pointed to the main challenges they faced during treatment implementation.